Wanting to or having to - a qualitative study of experiences and attitudes towards migrant screening for tuberculosis in Norway - Ingunn Nordstoga; Mona Drage; Tore Wælgaard Steen; Brita Askeland Winje (BMC, 2019)
Abstract Background This study assesses how tuberculosis (TB) screening is perceived by immigrants in Norway. Screening is mandatory for people arriving from high incidence countries. To attend screening, immigrants have to contact the health system after receiving an invitation by letter. The proportion of non-attenders is not known, and there are no sanctions for not attending. Generally, only persons who test positive receive test results. The study explores users' experiences, attitudes and motivations for attending or not attending TB screening, and perceived barriers and enablers. Methods We conducted six focus group discussions and three individual interviews with 34 people from 16 countries in Africa, Asia and Europe. Interviews were recorded and transcribed, and data was coded following a general inductive approach: All transcribed text data was closely read through, salient themes were identified and categories were created and labelled. The data was read through several times and the category system was subsequently revised. Results Most appreciated the opportunity to be tested for a severe disease and were generally positive towards the healthcare system. At the same time, many were uncomfortable with screening, particularly due to the fear and stigma attached to TB. All experienced practical problems related to language, information, and accessing facilities. Having to ask others for help made them feel dependent and vulnerable. Positive and negative attitudes simultaneously created ambivalence. Many wanted "structuring measures" like sanctions to help attendance. Many said that not receiving results left them feeling anxious. Conclusions In order to adapt the system and improve trust and patient uptake, all aspects of the screening should be taken into account. Ambivalence towards screening probably has a negative impact on screening uptake and should be sought reduced. A combination of ambivalence and a wish for "structuring measures" leads the authors to conclude that mandatory screening is a reasonable measure. However, since mandatory screening negatively impacts patient autonomy, and because of fear, stigma and practical problems, the health system should empower users by improving communication and access to services. In addition, it is recommended that negative test results are also communicated to the users.